SAFETY OF SAUCE PRODUCTS FOR HEALTH PURPOSES - ANTONENKO АRTEM; BAL-PRYLYPKO, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article notes the peculiarities of the use of dietary supplements and developed the technology of sauces using polydextrose, gum arabic, and protein-fat additives. Mathematical methods based on the physical and chemical parameters of emulsions and chemical composition determined the rational ratio in composite mixtures of protein-fat additive, gum arabic and polydextrose as 0.5:0.3:0.2. Through mathematical processing of experimental data, the regression level was determined, which describes the one-factor space of an independent complex indicator of quality from the concentration of the composite mixture. The rational concentration of the composite mixture in the finished sauce was determined, which is 15% of its mass, for which they have organoleptic, physico-chemical and structural-mechanical properties close to traditional sauces. The use by manufacturers of certain food additives to provide food products with specified organoleptic and structural-mechanical properties, as well as the desire to minimize costs, reduce the duration of the technological process to the deterioration of quality and the danger of consuming such products. The quality was determined based on the safety indicators of the new products in comparison with traditional analogues based on the content of heavy metals. From the microbiological indicators, the number of MAFAnM molds and yeasts, the bacterial group of Escherichia coli, pathogenic microorganisms, including parts of the genera Salmonella, Proteus and Staphyloccocus aureus. All indicators are determined in samples of sauces after preparation and storage. After 48 hours of storage, the count of mesophilic aerobic and facultative anaerobic microorganisms in sauce samples was, on average, 20 times below regulatory standards. The new sauces exhibited lower microbial levels than the control samples, attributed to an increased proportion of dry matter and bound moisture, which elevates osmotic pressure and inhibits microbial growth. No mold, yeast, coliform bacteria (BGKP), or pathogenic microorganisms were detected in the tested samples. The study confirmed that lead, copper, and zinc levels in the sauces remained within maximum permissible limits. Given their nutritional value, these sauces are recommended for inclusion in the diets of all population groups, particularly for workers in hazardous industries and residents of contaminated areas.